2005
DOI: 10.1291/hypres.28.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Impaired Aldosterone Response to Adrenocorticotropic Hormone and Prevalence of Hemodialysis in Type 2 Diabetic Patients without Azotemia

Abstract: The present prospective observational study was designed to assess the prevalence of hemodialysis in type 2 diabetic patients with an impairment of plasma aldosterone responsiveness to adrenocorticotropic hormone (ACTH). Sixty seven patients (43 men and 24 women) were selected. The inclusion criteria were age <65 years; presence of normoalbuminemia (serum albumin >3.6 g/dl); and absence of azotemia (serum creatinine ≤1.2 mg/dl in males, and ≤1.0 mg/dl in females). Soluble

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been reported that inadequate suppression of PAC after salt loading rather than the absolute value of PAC was associated with left ventricular hypertrophy in hypertensive subjects (9). Kigoshi et al reported that the impaired response of aldosterone to adrenocorticotropic hormone, but not the absolute value of aldosterone, predicted the progression to endstage renal failure among diabetic patients (27). Since we did not examine the value of PAC under these conditions, we could not determine the pathogenic role of aldosterone in chronic HD patients.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that inadequate suppression of PAC after salt loading rather than the absolute value of PAC was associated with left ventricular hypertrophy in hypertensive subjects (9). Kigoshi et al reported that the impaired response of aldosterone to adrenocorticotropic hormone, but not the absolute value of aldosterone, predicted the progression to endstage renal failure among diabetic patients (27). Since we did not examine the value of PAC under these conditions, we could not determine the pathogenic role of aldosterone in chronic HD patients.…”
Section: Discussionmentioning
confidence: 86%